(untitled) (Global Economic Review: Journal of Economics, Policy, and Business Development, 2025)
This research small business in the economy important the role of the population , in particular busyness provide and new work places in creation importance analysis to do focused . Small business not only there is work their places save to stay , maybe new and innovative work their places also important in creating source is considered . In the study small in business work of possibilities various kind aspects , including employee , manager and businessman as activity to conduct opportunities seeing is released . In the study small business new work places in creation to oneself typical characteristics, including labor basis , flexibility and innovation such as factors analysis Also, small in business of work advantages ( flexibility , growth opportunities , personal relationships ) and disadvantages ( big work size , less work right , social of privileges limited (also see Research results small business to develop aimed at politics improvement , population busyness increase and new work places create according to recommendations working exit for basis become service Also , the research results small in business work opportunities looking for individuals , small business of enterprises owners and managers , state organs and scientific research institutions for useful to be This is possible . research results small business in the economy role increase , population busyness provide and new work places to create aimed at efforts to support service does .